Study on the expression conditions and primary purification of recombinant P450 BM-3 monooxygenase - HUANG Jun; MEI Le-he; ZHONG Chun-long; DENG Fu-huang; YAO Shan-jing (浙江大学学报. 农业与生命科学版)
The optimum culture conditions of P450 BM-3 expression by recombinant Escherchia coli DH 5α were studied in detail. Using inoculum quantity corresponding to 1% of the culture medium, adding of 0.1mg·L-1 FeCl3 of the culture solution and rapid temperature shift from 37℃ to 42℃ as soon as OD578 reached about 1.0 and maintained for 5 hours, were proved to be the favorable conditions for growth of the bacteria and expression of the gene coding for P450 BM-3 monooxygenase. Purification of P450 BM-3 was investigated by two anion-exchange media DEAE-Sepharose FF, Resource Q. The results indicated that purification effectiveness of DEAE-Sepharose FF was inferior to that of Resource Q. The parameter of purification by Resource Q was optimized on ÄKTA explorer 100 system. By optimising the elution condition of P450 BM-3, the results showed that the purification factor was 2.12 and P450 BM-3 activity recovery was 30.1% through 0.3 mol· L-1, 0.5 mol· L-1 two-step NaCl elution.